Conceptual design of full carbon upcycling of CO2 into clean DME fuel: Techno-economic assessment and process optimization. (15th July 2023) - Gao, Ruxing; Zhang, Leiyu; Wang, Lei; Zhang, Chundong; Jun, Ki-Won; Ki Kim, Seok; Zhao, Tiansheng; Wan, Hui; Guan, Guofeng
Graphical abstract: Highlights: Conceptual design of four different CO2 -to-DME (CTD) processes is implemented. Rigorous process modelling and systematic techno-economic comparison are conducted. Direct hydrogenation of CO2 to DME is proved as a preferred and promising strategy for carbon mitigation. Enhanced system performances are achieved through further process integration and optimization. Abstract: To achieve efficient utilization of CO2 and produce clean alternative fuel, nowadays, CO2 -to-DME (CTD) technology is regarded as a feasible and promising solution. Considering that there is no consensus on the techno-economic performances of the different CTD processes, it is necessary to conduct a comprehensive and systematic comparison of the existing and emerging CTD technologies and to deeply explore the influence of the process integration on technical feasibility and economic profitability. In this study, we proposed four CTD processes via different routes, namely purified methanol-mediated (Case 1), water-containing methanol-mediated (Case 2), CO-mediated (Case 3) and direct CO2 hydrogenation routes (Case 4). The rigorous system modelling and comprehensive comparison of the process performances of four cases were implemented. From the technical perspective, Case 4 has the highest energy efficiency (77.42%), exergy efficiency (88.46%), and net CO2 mitigation rate (67.71%). From the economic perspective, Case 2 has the lowest total product cost (1327.14 $/tonne DME), whereas Case 4 has the lowest net CO2 mitigation cost (589.34 $/tonne CO2 ). Moreover, to further enhance the system performance of Case 4, we also proposed effective improvement measures for process optimization, which shows that the net CO2 mitigation rate is enhanced by 1.94%, while the net CO2 mitigation cost is reduced by 19.79 $/tonne CO2 .